2020
DOI: 10.7554/elife.62659
|View full text |Cite
|
Sign up to set email alerts
|

Cell non-autonomous regulation of health and longevity

Abstract: As the demographics of the modern world skew older, understanding and mitigating the effects of aging is increasingly important within biomedical research. Recent studies in model organisms demonstrate that the aging process is frequently modified by an organism’s ability to perceive and respond to changes in its environment. Many well-studied pathways that influence aging involve sensory cells, frequently neurons, that signal to peripheral tissues and promote survival during the presence of stress. Importantl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
69
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(69 citation statements)
references
References 161 publications
(197 reference statements)
0
69
0
Order By: Relevance
“…Rapid advances in aging research have identified several conserved signaling pathways that influence aging in organisms across taxa 1 . Recent work shows that many of these “longevity pathways” act through cell non-autonomous signaling mechanisms 2, 3 . These pathways utilize sensory cells—frequently neurons—to signal to peripheral tissues and promote survival during the presence of external stress.…”
Section: Mainmentioning
confidence: 99%
“…Rapid advances in aging research have identified several conserved signaling pathways that influence aging in organisms across taxa 1 . Recent work shows that many of these “longevity pathways” act through cell non-autonomous signaling mechanisms 2, 3 . These pathways utilize sensory cells—frequently neurons—to signal to peripheral tissues and promote survival during the presence of external stress.…”
Section: Mainmentioning
confidence: 99%
“…The extent and limits of retrograde signaling are an interesting topic of current research. It seems to have important implications, in epigenetics as well and for cell survival in young and old age, e.g., in communication between mitochondrion and cell nucleus and regulation of radical oxygen species (ROS), chromatin and histone formation, and for adjustments in metabolic and stress responses [35] [36]. In contrast, the term anterograde signaling is used for nuclear-encoded factors.…”
Section: Geneticsmentioning
confidence: 99%
“…In contrast to cytokines, which can represent growth factors as well, growth factors have always stimulating properties [45]. Besides, cell communication, often summarized with non-autonomous regulation, with its various molecules, e.g., growth hormones or via neurons with retrograde neuronal signaling up to brain structures like the hypothalamus and for example, the subsequent metabolic rearrangements in mitochondria, has a crucial role for environment adjustments and aging [35] [46].…”
Section: Stem Cellsmentioning
confidence: 99%
“…To gain new insights on how to bridge this gap, we focused our attention on intercellular communication (ICC). Dysregulation of ICC has been defined as a hallmark of aging 2,3 and has recently been proposed as one of the causes leading to the cell-to-cell stochasticity arising with age 4 . Well-known communication deregulations include inflammaging (a chronic low-grade age-associated inflammation) 5 , impaired immune surveillance 6 , increase in senescence-associated secretory phenotype (SASP) 7 , altered communication between stem cells and their niche 8,9 , remodeling of the extracellular matrix 10,11 and changes in endocrine and neuronal communication 12 .…”
Section: Introductionmentioning
confidence: 99%
“…Read counts/UMIs from the single-cell dataset are aggregated by cell types and conditions(1). Genes are then joined with our database of ligand-receptor interactions(2) to build all the potential cell-cell interactions that can occur between cell types(3). Statistical permutation tests are then performed to evaluate the…”
mentioning
confidence: 99%